Ordering of representational level adverbial modifiers in spoken Brazilian Portuguese - Pezatti, Erotilde Goreti (ALFA: Revista de Linguística, 2009)
Supported by the Functional Discourse Grammar theoretical model, as proposed by Hengeveld (2005), this paper aims to show that the order of modifiers of the Representational Level in spoken Brazilian Portuguese is determined by scope relations according to the layers of property, state-of-affairs and propositional content. This kind of distribution indicates that, far from being free-ordered as suggested by traditional grammarians, modifiers have a preferred position determined by semantic relations that may be only changed for pragmatic and structural reasons.